Determination of phosphorus additives in instant noodle samples by Phosphorus-31 nuclear magnetic resonance (31P-NMR) - Trung Quang Pham; Lan Anh Thi Nguyen; Nhung Thi Dao; Thao Thi Ta (Vietnam Journal of Science, Technology and Engineering, 2024)
Instant noodles are widely consumed in Vietnam and are especially popular among young people. In the production of instant noodles, phosphate additives are commonly added to enhance the crispiness and chewiness of the product. In this study, three phosphate species, including sodium pyrophosphate (SPP), sodium tripolyphosphate (STPP), and sodium hexametaphosphate (SHMP), in instant noodle samples collected from the Vietnamese market were rapidly analysed using the 31P-NMR method. The phosphate species in instant noodle samples were simply extracted using deionised water. For 31P-NMR measurement, a D2O/deionised water mixture (9:1) was added. Chlorpyrifos ethyl was used as an internal standard and the pH was adjusted to 9-10. The 31P-NMR spectra were then obtained in 1D mode using a pulse program that involved a 90o hard pulse. The method detection limits for SPP, STPP, and SHMP determination were 0.60, 0.30, and 0.74 mg/g, respectively. The repeatability of SPP in instant noodles was found to be smaller than 5%. The linearity was tested with R² (R-squared) values greater than 0.99 for all three analytes. The analysis of instant noodle samples revealed the presence of only SPP, a common additive known for its significant impact on enhancing food quality. The SPP content was estimated to be around 25-54% of the total phosphate, determined by UV-Vis based on the heteropoly blue phosphomolybdate complex.